Redke oblike raka in njihovi dodatni problemi - Marovič, Astrid (Placebo, 2023)
Rare cancers occur in fewer than six per 100.000 people per year, but together they account for about a fifth of all cancers in the European Union. Their incidence has been increasing in recent years. Although survival rates are improving, they are still lower than that of common cancers. The rarity of these diseases poses many problems for patients, healthcare professionals, and researchers. The patient's path to a correct diagnosis can often be lengthy due to the limited experience of doctors and the limitations of diagnostic methods, and access to specialized facilities can be logistically challenging. Clinical studies in the field of rare cancers have certain limitations, as they usually involve fewer patients. Drugs for rare cancers are often very expensive and not profitable to develop. Nevertheless, progress has been made in the field of rare cancers in recent years.
Keywords: incidenca; preživetje; Rak (medicina); Redke bolezni; redki raki; zdravila sirote